1997
DOI: 10.1103/physrevb.55.14554
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi-liquid states and pairing instability of a general model of copper oxide metals

Abstract: A model of copper-oxygen bonding and anti-bonding bands with the most general two-body interactions allowable by symmetry is considered. The model has a continuous transition as a function of hole-density x and temperature T to a phase in which a current circulates in each unit cell. This phase preserves the translational symmetry of the lattice while breaking time-reversal invariance and the four-fold rotational symmetry. The product of time-reversal and four-fold rotation is preserved. The circulating curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
614
2
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(649 citation statements)
references
References 92 publications
30
614
2
3
Order By: Relevance
“…120 The above neutron experiments appear to be consistent with more complicated circular-current states that do not break this symmetry. 90,121,122 Recently, however, one of the authors showed that this type of circular-current state is not stabilized with respect to the normal state in a wide range of the model parameters on the basis of systematic VMC calculations with refined wave functions for d-p-type models. Instead, SF states are stabilized in some parameter ranges.…”
Section: Comparison With Experiments (I) High-t C Cupratesmentioning
confidence: 99%
“…120 The above neutron experiments appear to be consistent with more complicated circular-current states that do not break this symmetry. 90,121,122 Recently, however, one of the authors showed that this type of circular-current state is not stabilized with respect to the normal state in a wide range of the model parameters on the basis of systematic VMC calculations with refined wave functions for d-p-type models. Instead, SF states are stabilized in some parameter ranges.…”
Section: Comparison With Experiments (I) High-t C Cupratesmentioning
confidence: 99%
“…(a) Diagram for the singular contribution to the one-particle self-energy with the uctuating (q; ). g's are the vertices which in microscopic theory [270] is shown to have important momentum dependence, but which gives negligible momentum dependence to the self-energy. (b) For 0 (q; ) which is momentum independent, a total vertex may sometimes be usefully deÿned, which has the same frequency dependence as Eq.…”
Section: Marginal Fermi Liquid Behavior Of the Normal Statementioning
confidence: 99%
“…As suggested by its different momentum dependence from its nodal counterpart, the antinodal pseudogap may have a different origin, which has been the subject for intense discussions in the literature [2][3][4][5][6][7][8][9] . Generally, as inferred from Supplementary Information, Fig.…”
mentioning
confidence: 99%